Integrated Analysis by Geophysical and Spatial Data to Identify the Formation of Kepuhlegundi Hot Spring on Bawean Island - Rafi Muhammad Erfand Dzulfiqar; Fajar M Haris Miftakhul; Ulumuddin Faqih; Purwanto M Singgih (Russian Journal of Earth Sciences, 2024)
Bawean Island is a result of volcanic activity in the back-arc volcanism zone located on the north side of Java Island. Bawean Island was formed due to the geological structure being controlled by the Paleogene-Neogene tectonic line in the Meratus Pattern. The mantle tearing resulted in the formation of the Bawean Arc. The Kepuhlegundi Hot Spring is a component of the volcanism product on Bawean Island. To analyze the formation of hot springs in more detail, we conducted magnetic method measurements and integrated the data with gravity satellite and Fault Fracture Density (FFD) methods. The three methods were used to determine the continuity of the mapped geological structures surrounding the hot springs. The FFD method can be used to map the weak zone of the hot spring, which is caused by the lineament surrounding it. The magnetic and gravity methods reveal anomalous contrasts that extend towards the hot springs in the direction of the structure. The magnetic and gravity methods reveal anomalous contrasts that extend towards the hot springs in the direction of the structure. Based on regional anomaly analysis, spectrum analysis indicates that the structure is located at a shallow depth of 15 to 80 meters. The drawing in each method shows a dominant orientation in the Northeast-Southwest direction, which corresponds to the orientation of the Meratus Structure Pattern. Kepuhlegundi Hot Spring is formed due to the control of geological structures, allowing hot fluids to flow through fractures as an aquifer.